Microstructures and electrochemical performances of Mm(NiCoMnAl)5-Mg2Ni hydrogen storage alloys prepared by casting and rapid quenching - Wang, H.; Tian, X.; Shang, T.; Naren, G.; Liu, Jian; Yun, G. (2016)
© 2016, Editorial Office of "Chinese Rare Earths". All right reserved. The as-cast Mm(NiCoMnAl)5-Mg2Ni composite hydrogen storage alloys were firstly prepared by two steps melting method. Then the as-cast Mm(NiCoMnAl)5-Mg2Ni alloy was treated by rapid quenching at different quenching rates. Finally, a series of rapid quenched Mm(NiCoMnAl)5-Mg2Ni alloys at different quenching rates were obtained. The microstructures and electrochemical properties of Mm(NiCoMnAl)5-Mg2Ni composite alloys were investigated by means of X-ray diffraction (XRD), scanning electron microscopy with energy dispersive spectrometer (SEM/ EDS) and electrochemical measurements. Microstructure investigation showed that the as-cast Mm(NiCoMnAl)5-Mg2Ni composite alloy is composed of the LaNi5 phase and a small amount of the Mg2Ni phase. However, the quenched composite alloys consist of the LaNi5 phase and the new phases of LaNi3 and La2Ni3. Moreover, the Mg element in the quenched alloys is mainly dissolved in the rich rare earth LaNi3 phase. Finally the (La, Mg) Ni3 phase is formed. Electrochemical analysis showed that the activation performance, the maximum discharge capacity, discharge potential characteristic and cycle stability of Mm(NiCoMnAl)5-Mg2Ni composite alloys can be improved by appropriate rapid quenching technology. But the rapid quenching rate is too high, the above performances of alloys are worse. Among the alloy samples studied, the maximum discharge capacity of the quenched composite alloy at 15 m· s-1 is the best and its value is 303.5 mAh· g-1. This value increases by 3.3% compared to that of the as-cast alloy. Furthermore, the quenched Mm(NiCoMnAl)5-Mg2Ni alloy at the quenching rate of 20 m· s-1 exhibits the best cycle stability. The capacity retention after 80 cycles of the composite alloy is 98.3% and increases by 11.9% compared to that of the as-cast alloy.